The effect of participation in an activity oriented science curriculum development workshop on the attitude of elementary teachers in Trinidad and Tobago - Fraser-Abder, Pamela
This study investigated the extent of attitudinal change towards the teaching of science in primary school teachers (N=35) in Trinidad and Tobago during an activity-oriented science curriculum development workshop. The model used during the workshop attempts to: 1) incorporate some aspects of science content development, manipulative hands-on experiences, video-taping, development of self-confidence, teach-reteach methodology, and supervisor, peer, and self-evaluation strategies; and 2) to modify the teachers' affective, cognitive, and behavioural responses to primary science teaching. Results obtained from a 27-item instrument (measuring science knowledge, use of science equipment, interest in science, and apprehension about science teaching) indicate development of positive attitudes in each of the four areas measured. The study shows that the model was effective in producing the desired attitudinal changes and strongly suggests the use of the model in attitude modification research among inservice primary school teachers. Objectives and activities for each day of the workshop are included
Keywords: Curriculum development